Electronic Commerce 2012 a managerial and social networks perspective - Turban, Efraim (Harlow Pearson, 2012)
Explore the many aspects of electronic commerce through a managerial perspective. Electronic Commerce provides a thorough explanation of what EC is, how it?s being conducted and managed, and how to assess its opportunities, limitations, issues, and risks?all from a managerial perspective. To keep pace with today?s ever-changing technology, the seventh edition has been streamlined?removing material that?s no longer relevant, while still providing information on the hottest topics in the field.
Includes index
Keywords: Electronic Commerce